Faktor Psikososial dan Aktivitas Kerja pada Perawat ICU serta ICCU dengan Nyeri Punggung Bawah - Gandu Eko Julianto Suyoso (Puslitbang Sinergis Asa Professional, 2019)
Background: Low back pain was one of many musculosceletal disorder that were still suffered by nurses. Low back pain caused by many factor, partially or simultaneuosly. Some of those factor are psychosocial factor and occupational activity factor. Psychosocial factor consisted of job demand, job control, social support and job satisfaction. Occupational activity factor in this study was lateral patient transfer. Those factor were still neglected by some of hospital employer. Purpose: The aim of this study is to analyze the association of psychosocial factor (job demand, job control, job satisfaction, social control), occupational activity control (lateral patient transfer) and nurse’s low back pain. Methods: This cross sectional study held in ICU and ICCU unit at 3 hospital in Jember. Data was collected through questionairres that adopted General Nordic Questionairre (QPSNORDIC) also MJS (Measure of Job Satisfaction) and through observation by utilized REBA (Rapid Entire Body Assessment) scoring method.. Results: Bivariat analysis showed that nurse’s low back pain have association with nurse perception about job demand (r=0,414), nurse perception about social support (r=0,510), nurse perception about job satisfaction (p=0,401), association with nurse perception about job control (r=0,333), lateral patient transfer (r=0,439). Conclusion: Nurses Low Back Pain have a strong association with nurse perception about job demand, nurse perception about social support, nurse perception about job satisfaction; a weak association with nurse perception about job control.